Stereocontrolled Total Synthesis of Polygalolide A. Issue 7 (13th May 2013) - Yamada, Hitomi; Adachi, Masaatsu; Isobe, Minoru; Nishikawa, Toshio
Abstract The total synthesis of polygalolide A, a secondary metabolite that was isolated from a Chinese medicinal plant, is reported. A key issue in this synthesis was construction of an oxabicyclo[3.2.1] skeleton, which was solved by the development of an intramolecular Ferrier‐type C‐glycosylation of a glucal with siloxyfuran as an internal nucleophile. The substrate was prepared from D‐glucal by the introduction of trimethylsilylacetylene and siloxyfuran groups. Although C‐glycosylation did not occur under the conditions found from model experiments, further examination revealed that the combination of trimethylsilyl trifluoromethanesulfonate (TMSOTf) and 2, 4, 6‐collidine successfully afforded the desired product as a single diastereomer. The siloxy group at the C3 position played a crucial role in the stereocontrol of this reaction. The product was further transformed into a tetracyclic compound as follows: The vinyl ether and acetylenic moieties were reduced and the siloxy group was removed with a Barton–McCombie reaction. The construction of the six‐membered ether and the γ‐lactone provided the tetracyclic compound. Finally, a phenolic moiety was introduced by using a Mukaiyama aldol reaction to furnish polygalolide A.